2009
DOI: 10.1093/alcalc/agp004
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Gestation and Breastfeeding: Selenium as an Antioxidant Therapy

Abstract: These results suggest that selenium could be effective in neutralizing the damage of ethanol consumption during gestation and lactation in pups since it repairs selenium levels in liver as well as the activity of scavenging enzymes and peroxidation protein products. In serum, Se also recovers GPx activity and increases the levels of Se that are available to other organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
53
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 30 publications
8
53
0
1
Order By: Relevance
“…The source of radiation was a Se electrodeless discharge lamp. The instrumental operating conditions and the reagents are the same as those we used in the previous paper by Ojeda et al (2009). Samples: serum samples were diluted fivefold in 0.2% v/v HNO 3 and 0.2% Triton X-100 solutions and urine samples were diluted 1:2 v/v.…”
Section: Se Analysismentioning
confidence: 99%
“…The source of radiation was a Se electrodeless discharge lamp. The instrumental operating conditions and the reagents are the same as those we used in the previous paper by Ojeda et al (2009). Samples: serum samples were diluted fivefold in 0.2% v/v HNO 3 and 0.2% Triton X-100 solutions and urine samples were diluted 1:2 v/v.…”
Section: Se Analysismentioning
confidence: 99%
“…A non-signifi cant decrease in the GPx activity indicated a lowered demand for the conversion of peroxides to water as a result of the changes in the SOD activity. In contrast to retinoic acid treatment, in ethanol-treated rats, the GPx activity increased signifi cantly in the offspring (Ojeda et al, 2009). It is well known that GPx inactivation and SOD downregulation cause an increase in oxidative stress (Li et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…According to what we have previously reported [8], the effects of ethanol exposure during gestation and lactation on folic acid intestinal absorption showed that intestinal folate absorption appears to be upregulated in suckling rats. Our research group has also found, in pups exposed to ethanol and supplemented with folic acid during the gestation and lactation periods, an increase in intestinal longitude (control, alcohol and alcohol plus folic acid: 53.56 ± 1.49, 43.7 ± 0.92 and 48.36 ± 1.69 cm, respectively) and intestinal mucosa weight (control, alcohol and alcohol plus folic acid: 15 ± 0.8, 12 ± 0.8 and 15 ± 1 mg/cm 2 , respectively).We have recently described that ethanol decreases selenium (Se) retention in dams, affecting their gestational parameters and the body weight, and the antioxidant balance of their progeny [9][10][11][12]. This essential trace element is of fundamental importance to health due to the antioxidant, anti-inflammatory and chemopreventive properties attributed to its presence in at least 25 selenoproteins such as glutathione peroxidase (GPx) [13].…”
mentioning
confidence: 99%
“…57, No. 6, 2011 SELENOMETHIONINE ABSORPTION IN DUODENUM OF ETHANOL-EXPOSED RAT OFFSRPING 709 their intestinal development; moreover, our research group has found that Se or Se plus folic acid supplementation during gestation and lactation could prevent liver oxidative damage in the pups, thus improving their development and health [10,11].At present, a limited number of studies have explored Se uptake in offspring rats [16] or infants [17,18], and there are no reports concerning this in ethanol-exposed pups. In this context, Anan et al (2009) [19] found that suckling pups mainly obtained Se presenting in breast-milk in organic form as Se-Met.…”
mentioning
confidence: 99%
See 1 more Smart Citation